2019
DOI: 10.12669/pjms.35.4.350
|View full text |Cite
|
Sign up to set email alerts
|

The effects of simulation-based education on initial neonatal evaluation and care skills

Abstract: Objective: Neonatal evaluations performed at the very first minutes following postpartum are the most important steps in deciding for neonatal resuscitation. Therefore, the newborn initial care and evaluation notion and skills of midwives in the delivery hall are quite important. The study was planned to determine the effects of simulation education on newborn evaluation and care skills in midwifery students. Methods: This is a quasi-experimental study. The population of the study was composed of the 4th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The study of Karakoc A et al confirmed the use of simulation to push healthcare education toward patient-centered care to improve patient safety. 3 In addition, Krathwohl verified in his article on Bloom’s Taxonomy that simulation-based healthcare education enhanced students’ self-efficacy and practical skills, which positively boosted patient safety. 19 Moreover, Naidu et al 15 , and Faggioni et al 16 added that simulation could minimize students’ learning curve and introduce well-prepared learners to health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Karakoc A et al confirmed the use of simulation to push healthcare education toward patient-centered care to improve patient safety. 3 In addition, Krathwohl verified in his article on Bloom’s Taxonomy that simulation-based healthcare education enhanced students’ self-efficacy and practical skills, which positively boosted patient safety. 19 Moreover, Naidu et al 15 , and Faggioni et al 16 added that simulation could minimize students’ learning curve and introduce well-prepared learners to health care.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Simulation-based education provides trainees an opportunity to practice practical cases in a safe learning and teaching environment. 2 , 3 Importantly, simulation ties the knowledge to practice and grooms the healthcare trainees to be safe and efficient in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%
“…After statistical analyses of the students from both groups, it was determined that those who had received simulation-based training (experimental group) were more competent than the control group. 22 Another study was found in support of simulation, which was conducted in the emergency department to determine the impact of implementing scenarios’ simulation on idle and service time.…”
Section: Methodsmentioning
confidence: 99%